2020
DOI: 10.1038/s41598-020-76814-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the construction and infiltration strategies of social bots in sina microblog

Abstract: Nowadays, millions of people use Online Social Networks (OSNs) like Twitter, Facebook and Sina Microblog, to express opinions on current events. The widespread use of these OSNs has also led to the emergence of social bots. What is more, the existence of social bots is so powerful that some of them can turn into influential users. In this paper, we studied the automated construction technology and infiltration strategies of social bots in Sina Microblog, aiming at building friendly and influential social bots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Shen et al (2023) conducted a similar study by collecting 3,816 random bot accounts related to the Russian–Ukrainian conflict from 17 February to 17 March 2022 and concluded that the average number of bot account followers was 988, and the median number was 174. In another study, 96 bots were deployed on a social platform and gained 5,546 followers in total over the course of 42 days (Wang et al, 2020). As such, @UAWeapon stands out from similar ones due to its rapid growth in followers within a relatively short period of time, and therefore, it was selected as the subject of this study.…”
Section: Methodsmentioning
confidence: 99%
“…Shen et al (2023) conducted a similar study by collecting 3,816 random bot accounts related to the Russian–Ukrainian conflict from 17 February to 17 March 2022 and concluded that the average number of bot account followers was 988, and the median number was 174. In another study, 96 bots were deployed on a social platform and gained 5,546 followers in total over the course of 42 days (Wang et al, 2020). As such, @UAWeapon stands out from similar ones due to its rapid growth in followers within a relatively short period of time, and therefore, it was selected as the subject of this study.…”
Section: Methodsmentioning
confidence: 99%
“…The group-based social bot detection method utilizes the structural differences between the social graphs generated by humans and bots. The relationships that are used to build the social graph are usually friend relationships 33 , following/follower 34 , 35 , retweet/retweeted 36 . The detection mechanism is to use the homogeneity of social networks, in another word, the neighbor nodes of the bot tend to be bots, and the neighbor nodes of the human tend to be humans 34 , 37 – 39 .…”
Section: Related Workmentioning
confidence: 99%
“…After creating accounts, the controllers may use network crawlers and machine learning to build up the interaction and feedback capabilities of social bots when communicating with human users. According to Wang et al [8], the controllers use network crawlers to collect four types of information about human users: social network information, profile information, posts, and comments. The information gathered by a network crawler would be saved in a database.…”
Section: Deployment Of Social Botsmentioning
confidence: 99%
“…This process can help social bots confirm the object of an interaction. According to related studies, at this stage, social bots may retweet content to users with the same stance, and bots may also intentionally retweet content to users with opposite stances to trigger an opinion conflict, which may draw more attention from human users [8].…”
Section: Influence Release Stage Of Social Botsmentioning
confidence: 99%